Trade capacity building : critical for development (OECD Pub. ParisFR, 2003)
Looks at what trade capacity building is and why support from the international community is so important. Reviews progress to date and sets out the remaining challenges for the trade and development communities. Concludes by showing what the OECD can do to help support international initiatives on trade capacity building.
Bibliography: p. 7